EL RETRATO FOTOGRÁFICO EN EL SIGLO XXI. NUEVA EDAD DE ORO - Moreno Vera, Juan Ramón (2013)
We consider the beginning of the 21th century a new golden age for photographic portraiture because of its massive appearance between users becoming a deeply-rooted social custom. In the study we analyze some cultural functions that portraiture fills as reconstructing our personal memory through images of our lives, to be used as a mass media in terms of communication and publicity thank to internet and the social networks, and lastly its artistic view where portraiture is completely free, linking its borders to other photographic genres, and assuming different subjects that have nothing to do –in principle- with portraiture.